Values on the background of nutrition on seeds in grains F1 - F2 сorrelation of economic characteristics (Journal of Universal Science Research, 2023)
Particular importance in the article is the research conducted in the genetic collection of cotton at the National University of Uzbekistan. The correlation between value traits, including quantitative traits, in the hybrids of isogenic and introgressive lines of the Cotton Genetic Collection of the National University of Uzbekistan has been positively inherited.